2022 ALUMINUM ALLOY COLD/HOT-ROLLED SHEETS STRENGTH AND ANISOTROPY ANALYSIS - LIAN LiangChong; JIANG RuiBin; WU Hao (Jixie qiangdu)
2022 alloy has some characteristics of high strength,resistance to damage,can strengthen aging,When used in the next generation of supersonic aircraft skin and armored fighting vehicles and other fields,hot rolled and cold rolled are distinguish due to the different incoming member shapes.After aging treatment,hot-rolled plates tensile and yield strength higher than cold rolled sheet,but its elongation decreased.Under the same kind of rolling state,the perpendicular to the rolling direction of tensile higher than the yield in the rolling direction,but,elongation is reduced.By optical and transmission electron microscopy find hot rolled sheet grain relatively small and recrystallized grains increase than cold rolled sheet.The precipitation of hot-rolled plate small,densely distributed in the aluminum matrix compared to sheet cold-rolled,in macro the reaction to the higher tensile strength and hardness.